Securing the Cloud: Privacy, Policy, and AI-Driven Cybersecurity Solutions - Rinaldo (Digitus : Journal of Computer Science Applications, 2024)
As cloud computing becomes the backbone of modern digital infrastructure, cybersecurity has emerged as a critical concern across public and private sectors. This narrative review investigates the multifaceted threats, defense strategies, and policy implications associated with cybersecurity in the cloud environment. Literature was systematically sourced from Scopus and Google Scholar using keywords such as "cybersecurity", "cloud security", "AI for cybersecurity", and "data privacy", with inclusion criteria focusing on recent, peer-reviewed studies. The review revealed that data security threats—particularly DDoS attacks, ransomware, and data leakage—are on the rise, with over 40% of organizations reporting incidents in the past two years. Privacy protection varies globally, depending on both technological implementations and regulatory frameworks like the GDPR. Strategies such as encryption, AI-based anomaly detection, and Zero Trust architecture are proving vital in threat mitigation. Yet, systemic challenges—such as policy inconsistency, digital skill gaps, and uneven infrastructure—hinder progress, particularly in developing regions. The discussion emphasized that successful implementations often involve coordinated governance, robust public-private partnerships, and inclusive education strategies. This study concludes by calling for targeted policy reform, investment in digital capacity building, and deeper research into scalable cybersecurity models for vulnerable contexts. These findings underscore the urgency of constructing adaptive and inclusive cybersecurity frameworks to support safe and resilient digital transformation.